Feasibility of a Sheep Welfare Assessment Tool in the Pre-export Phase of Australian Live Export Industry - Collins, Teresa; Anthony, Ursula M. C.; Dunston-Clarke, Emma J.; Fleming, Patricia A. (Frontiers in Animal Science, 2021)
Sheep are exposed to numerous stressors and environments during the pre-export phase of the live export industry and establishing how exposure influences behaviour, health and demeanour prior to sea transport is the first step towards testing the suitability and practicality of animal welfare measures. Pen-side behavioural and health measures were collected, and Qualitative Behavioural Assessment (QBA) of video footage was conducted on 240 merino wethers originating from four farms. Wethers were assessed at four locations prior to export: on-farm, upon arrival to the feedlot (Fe1), prior to departing the feedlot (Fe2) and 30min post loading onto a ship. Videos were edited to provide 48 30-45s clips which were scored by 12 assessors against 10 demeanour terms and analysed using Principal Components (PC) analysis. Repeated Measures ANOVAs tested for variation in PC scores and square-root transformed behaviour and health measures across locations. Seven health and behaviour measures significantly varied across the four locations, with vocalising peaking on farm, drinking, eating and resting behaviours peaking at Fe1 and ruminating at Fe2, while the percentage of wethers with ocular discharge and lameness peak on ship, with low levels of these health issues recorded overall. For QBA, PC1 explained 30.5% of the variability, with agitated and nervous loaded to one end of the axis and calm and relaxed loaded to the opposing end. PC2 explained 24.5% of the variability, with interested, alert and sociable loaded to one end of the axis and lethargic and bored loaded to the opposing end. Spearman’s rank correlations between PC scores, behaviour and health measures found when wethers were scored to be more calm and relaxed, they were more likely to be eating, ruminating and resting, while those who were scored to be agitated and nervous, and bored and lethargic were also likely to vocalise. Determining how wethers respond to the different environments in the immediate pre-export phase of the journey informs on their welfare and the practicality of using a welfare assessment tool.